Rola kapitału intelektualnego w budowaniu przewagi konkurencyjnej firmy - Serafin, Krystyna (The Role of Intellectual Capital in Building Competitive Advantage, 2005)
This paper discusses the problem of intellectual capital (IC), human and organizational competencies and their management. Basing on given definitions the components of IC are presented and analized. Methods for IC measurement and techniques of competency identification are also given herein. A proper definition of competencies and their relation with company strategy results with a competitive advantage of the enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 383-393